Evaluation of CDL- CQI monitoring mechanism in open distance learning (ODL) of materials science and technology course during COVID-19 pandemic / Suzana Ratim ... [et al.] - Ratim, Suzana; Zakaria, Rosnah; Gisip, Judith; Ibrahim, Norazura; Jani, Nur Aimi (UiTM Press, 2024)
The COVID-19 pandemic has necessitated a rapid shift to online and distance learning modalities that may impact the quality assurance of teaching and learning process, particularly in higher education. This study focuses on the evaluation of a Closing the Loop - Continuous Quality Improvement (CDL-CQI) through monitoring mechanism implemented in an Open Distance Learning (ODL) of Materials Science and Technology programme. The primary objective is to evaluate the educational quality among the ODL students while being at home during COVID-19 pandemic. A comprehensive assessment of the CDL-CQI monitoring mechanism was conducted by employing a mixed-methods approach. Quantitative and qualitative data were gathered through various parameters such as examination grade, surveys and feedback , outcomes-based education-student centred learning (OBE-SCL), course-program-learning outcomes and soft skills. The CDL-CQI results indicated a statistically significant improvement of GPA grade in learning outcomes with the implementation of these monitoring tools. Learners reported increased engagement , enhanced self-directed learning skills, and improved interaction with course materials in ODL. The findings suggested that CDL-CQI tools have a positive effect on the quality of education in ODL environments. The implications of this study extend to both educational practitioners and policymakers involved in curriculum reviews. The results underscore the potential of CDL-CQI tools to foster a more dynamic and responsive learning environment, ultimately leading to enhanced learning outcomes attainment. By integrating these monitoring tools strategically, educators can better tailor their instruction and support to individual student’s needs.